Characterisation of emerging Campylobacter spp. from broiler chicken and chicken meat in Selangor and their antibiotic resistance - Sinulingga, Teguh Suranta (2014)
Campylobacters have been recognized as the most common bacteria causing gastroenteritis in humans. Campylobacter jejuni and C. coli are the most isolated species from animals and cases of human campylobacteriosis. However, the common isolation technique used in laboratories usually does not support the growth of other, potentially pathogenic non-jejuni, non-coli Campylobacter species. The application of an isolation technique such as the Cape Town protocol developed by Le Roux and Lastovica (1998) can lead to the isolation of other Campylobacter species. The members of these non-jejuni and non-coli Campylobacter species discovered are termed as emerging Campylobacter species due to increase in incidence in humans since its first introduction; they consisted of five species and have been recognized as important pathogens in humans and animals. In Malaysia, most of the studies were on isolated C. jejuni and C. coli and almost no study on isolated emerging Campylobacter species have been done. Thus, this present study was undertaken to determine the occurrence of emerging Campylobacter species in broiler chicken and chicken meat and their antibiotic resistance patterns. Two hundred and ten cloacal swab samples were taken from broiler chickens from seven different farms within Selangor. The samples were subjected to Cape Town protocol which combines membrane filtration onto antibiotic free blood agar plates and incubated at 37oC in hydrogen enriched micro-aerobic atmosphere. Campylobacter were presumptively identified by biochemical tests and confirmed by using multiplex PCR. A hundred and seven of the chickens (50.9%) were positive for Campylobacter. Among the isolates, C. jejuni was the most isolated species (69.5%) followed by C. coli (16.2%). Campylobacter fetus and C. upsaliensis were the only emerging Campylobacter species isolated in this study, 11 (9.3%) and three isolates (2.5%) respectively. The prevalence of Campylobacter in broiler chicken raised in open house system farms were found higher (70%) compared to broiler chicken raised in close house system farms (3.3%). Close house system farms apply strict bio security measure and hygiene practice that able to prevent Campylobacter transmission from environment to broiler flocks. To determine the occurrence of emerging Campylobacter species in chicken meat, 109 chicken meat samples were collected from 11 wet markets and five supermarkets in Selangor. Thirty three samples (30.3%) were found positive for Campylobacter. Twenty of Campylobacter-positive isolates (60.6%) were identified as C. jejuni, while five isolates (15.1%) were C. coli. Campylobacter fetus was the only emerging Campylobacter species isolated in this study, at 24.3% or eight isolates. The prevalence of Campylobacter isolated from supermarkets was higher (68%) than those from wet markets (14.3%). This may happen due to the different way of displaying of chicken meat; where in the wet market, chicken meat were only displayed in room temperature that provokes Campylobacter to enter viable but non culturable (VBNC) condition that made them not able to be isolated by plating method used in this study. An antibiotic susceptibility test was conducted to determine the antibiotic resistance pattern of these Campylobacter isolates. A total of 140 Campylobacter isolates were tested against 12 antibiotics by disc diffusion method. A total of 115 (97.4%) of Campylobacter isolated from broiler chicken and 33 (100%) of Campylobacter isolated from chicken meat were found resistant to one to ten antibiotics. In broiler chicken, more than 50% of Campylobacter isolates were found resistant to ampicillin, tetracycline, ciprofloxacin, nalidixic acid, enrofloxacin with the highest resistance was to nalidixic acid (79.6%) and the lowest resistance was to chloramphenicol (0.8%). In chicken meat, more than 50% of Campylobacter isolated from chicken meat were found resistant to trimethoprim/sulfamethoxazole, ampicillin, erythromycin, ciprofloxacin and nalidixic acid with the highest resistance was to ampicillin (87.8%) and the lowest resistance was to gentamicin (9.0%). Multidrug resistance (MDR) Campylobacter was observed in this study, 77.1% and 66.6% of Campylobacter isolated from broiler chicken and chicken meat respectively were resistant to three or more antibiotics. Overall, the finding from this study indicated that Cape Town protocol is useful to isolate not only C. jejuni and C. coli but also other Campylobacter species. Campylobacter jejuni and C. coli were still dominant Campylobacter species in broiler chicken and chicken meat. Although the method is somewhat laborious, it however enables to isolate some emerging Campylobacter species (C. fetus and C. upsaliensis) which may cause the occurrence of diseases in humans. The public health significance of this study is the finding of other Campylobacter species in chickens and chicken meat that may cause gastroenteritis and other infections in humans and the presence of high MDR Campylobacter species which could compromise treatment in humans if required. Also from this study it is observed that there is a need to create awareness among farmers on the increase in antibiotic resistance and the prudent use of antibiotics in chickens among farmers.